Case studies in microbiology : a personal approach - Anderson, Rodney P.; Young, Linda, 1961- (Hoboken, NJ : Wiley, 2012)
'This first edition text developed and evolved to meet three pedagogical goals we deemed essential for those studying allied health and are pre-professional. The use of microbiology case studies were modified to maintain their value as tools that result in critical thinking and knowledge retention while providing a more realistic context for preparing future health care professionals. Consequently, the text has real life, personally-oriented microbiology cases appropriate for those in nursing, pharmacy, and other allied health disciplines (pre-med, pre-PA, CLS, etc.). This format presents material as a story about the patient as well as information regarding their family circumstances, personal characteristics, and individual motivations'--Provided by publisher.
and Roll!3. Genital Herpes Herpes Simplex Virus Type II: A Bad First Impression.4. Genital Warts and Cervical Cancer Human Papilloma Virus: The Domino Effect.5. Candidiasis Candida albicans: An Ongoing Problem.6. Trichomoniasis Trichomonas vaginalis: An Infectious New Lifestyle.II. Nosocomial Infections.1. Toxic Shock Syndrome Staphylococcus aureus TSS toxin: A Nose for Trouble.2. Hepatitis C Hepatitis C Virus: A Hep C History Lesson.3. Septecemia Staphylococcus aureus: The Super Bug.III. Family Health Care.A. Pediatric Infections.1. Fifth's Disease Human Parvovirus B19: A New Twist on a Childhood Disease.2. Chicken Pox Varicella Zoster Virus: Why Did the Chicken Cross the Road?3. Hand Foot and Mouth Disease Coxsackie Virus A17: Hand, Foot and Mouth Disease.4. Scarlet Fever Streptococcus pyogenes: Seeing Red.5. Bronchiolitis Respiratory Syncytial Virus:'Tis the Season.6. Swimmer's Ear: Pseudomonas aeruginosa: Splash.B. Childbearing-Related Infections.1. Group B Strep Colonization Streptococcus agalactiae: Special Delivery2. Listeriosis Listeria monocytogenes: A Cookout Concern.C. Geriatric Infections.1. Shingles Varicella Zoster Virus: The Second Time Around.2. Gonorrhea: Neisseria gonorrheae: An Unexpected Outbreak.IV. Food Safety.1.Staphylococcal Food Poisoning Staphylococcus aureus enterotoxin: No Thanks, I'll Have the Turkey.2. Bacterial Meningitis Enterobacter sakazaki: Danger in the NICU.V. Regionally-Acquired Infections.1. Lyme Disease Borrellia burgdorferi: An Infectious Vacation.2. Hanta Virus Pulmonary Syndrome Sin Nombre Virus: Rain, Rain, Go Away.
Machine generated contents note: I. Community-Acquired Infections.A. Skin, Eyes and Underlying Tissues.1. Boils Staphylococcus aureus (MSSA): A Homeless Hazard.2. Impetigo Staphylococcus aureus (MRSA): The Funk.3. Folliculitis Staphyolococcus aureus (MRSA): Hats Off to MRSA.4. Osteomyelitis Polymicrobial Infection: Trouble is Afoot.5. Necrotizing Fasiitis Streptococcus pyogenes: Down on the Farm.6. Viral Conjunctivitis Adenovirus: My What Pretty Eyes You Have!7. Post-operative osteomyelitis Pseudomonas aeruginosa: He Did It His Way.8. Dermatophytic Fungi Tiichophyton: The Tat Is Where It's At.9. Cellulitis Staphylococcus epidermidis: A Persistent Pimple.B. Nervous System.1. Meningococcal Meningitis Neisseria meningitides: Life in the Meningitis Belt.2. Rabies Rabies Virus: The Flying Mouse.3. West Nile Fever West Nile Virus: Vacation Headaches.C. Cardiovascular and Lymphatic System.1. Sepsis Streptococcus pneumoniae: A Common Opportunistic Pathogen.2. Rheumatic Fever Streptococcus pyogenes: Unhappy Returns.3. Tularemia Fransicella tularensis: Bunny Bits.4. Rocky Mountain Spotted Fever Rickettsia rickettsii: The Black Measles.5. Mononucleosis Epstein Barr Virus: Pucker Up.6. Toxoplasmosis Toxoplasma gondii: Toxoplamosis-Don't Blame Fluffy.D. Respiratory System.1. Strep Throat and Scarlet Fever Streptococcus pyogenes: Strawberry Red.2. Influenza Influenza A Virus (H1N1): An Evolving Situation.3. Q Fever Coxiella burnetii: Q Fever-An Occupational Hazard.4. Viral Pharyngitis Adenovirus: Swimming Pool Blues.E. Digestive System.1. Shigellosis Shigella sonnei: Hand Washing ABCs.2. Clostridium difficile-Associated Diarrhea Clostridium dificile: A Distressing Side Effect.3. Hepatitis A Hepatitis A Virus: Hold the Onions.4. Viral Gastroenteritis Norovirus: Diarrhea 101.5. Giardiasis Giardia lamblia: An Uninvited Party Guest.F. Urinary and Reproductive Systems.1. Cystitis Escherichia coli: The Honeymoon Is Over.2. Gonorrhea Neisseria gonorrheae: Sex, Drugs and Rock
Keywords: Clinical Medicine -- methods -- case reports; Clinical Medicine -- methods -- Examination Questions; Microbiological Phenomena -- Case Reports; Microbiological Phenomena -- Examination Questions